Nuclear and Molecular Imaging Modalities for Predicting Calcific Aortic Valve Disease Progression in Animal Models - Farber, Gedaliah (Université d'Ottawa / University of Ottawa, 2020)
Introduction and Objectives Calcific aortic valve disease (CAVD) is the most common valvular disease, accounting for 50% of all valve disorders and is the third most common cardiovascular disease following coronary disease and hypertension.[1,2] Currently, there is no pharmacological agent capable of reversing or slowing down the progression of CAVD and treatment of severe cases consists of surgical repair or valve replacement[2]. Hence, there is a crucial need for earlier detection using predictive biomarkers that will allow for preventative intervention as opposed to post-symptomatic disease treatment or management. Namely, one target of particular interest is the expression of matrix metalloproteinases (MMPs) (specifically MMP-1, -2, and -9) which are upregulated in CAVD prior to calcification events and have been previously shown to serve as an attractive molecular imaging target.1–3 The primary objective of this study is to assess the feasibility of detecting biomarkers of CAVD by various in vivo imaging modalities, such as PET and echocardiography. In addition, this study assesses disease progression in various mouse strains to qualify an appropriate CAVD animal model. Methods In vivo and ex vivo imaging of C57Bl/6 and ApoE-/- (n = 8 per strain cohort) mouse models are used to link unique features of matrix remodelling with CAVD progression. At baseline and longitudinal follow-up (4, 8, and 12 months), in vivo hemodynamic impairment is assessed through echocardiography, and calcification and MMP activity are measured using PET with a series of radiotracers: [18F]NaF for calcification, [18F]BR351 for the molecular targets of MMP-2 and -9, and [18F]FMBP with molecular target specificity for MMP-13. Following imaging, aortic valve (AV) tissue is harvested, sectioned, and analyzed for calcification, inflammatory markers, collagen types, and MMP activity in AV leaflets. Tracer autoradiography, immunofluorescence, and in situ zymography are used to confirm in vivo imaging results with improved resolution and quantification in valves. Histological sample preparation, experimentation, and analyses are then repeated in human AV tissue samples for relative comparison of biomarker expression in animal models. Results Echocardiography suggests positive signs of disease progression in experimental animal models. In comparison to WT, ApoE-/- mice show: increased peak velocity (p<0.0001), decreased aortic valve area (p<0.001), and irregular valve dynamics. [18F]NaF PET imaging shows expected bone uptake and low calcium-burden in young and WT animals. [18F]FMBP shows increased uptake in the valve area of diseased models at later timepoints, 1.530 compared to <0.001 %ID/g (p<0.005), in disease vs control animals respectively. Furthermore, confirmation of sought-after biomarkers has also been assessed by analysis of various histological sample preparations including the presence of leaflet calcification, upregulation of MMP-2, -9, and -13, matrix remodelling, lipids, inflammatory markers, and activated MMP expression. Conclusion Findings from this study suggest that molecular imaging techniques using target-specific radiotracers, as well as echocardiography for assessment of hemodynamic impairment, are feasible solutions in predicting disease onset in CAVD specific animal models.
Keywords: CAVD; aortic valve; valvular calcification; matrix metalloproteinase(s); nuclear imaging; PET; Positron Emission Tomography; matrix remodelling; molecular imaging; calcification; aortic stenosis; echocardiography